Beekeepers' intentions to adopt resilience strategies for climate change: a comparative and integrated approach using the theory of planned behavior and protection motivation theory - Ouertani, Emna; Erraach, Yamna; Arfa, Lamia; De-Magistris, Tiziana; Ornelas Herrera, Selene Ivette; Kallas, Zein (Frontiers in Climate, 2025)
Beekeeping plays a vital role in global food security, contributing to the pollination of up to 30% of global food production and ensuring the sustainability of food supplies worldwide. However, climate change has significantly impacted beekeeping in recent years, affecting honeybees, pollination, and honey harvesting. Due to the effects of climate variability, which impose environmental strain on bees and beekeepers, modifications in management strategies and agricultural practices are essential to enhance biodiversity, guarantee agricultural sustainability, and ensure food security. This study aims to investigate the factors influencing beekeepers' intentions to adopt resilience strategies in response to climate change using protection motivation theory (PMT), the theory of planned behavior (TPB), and an extended PMT model. The study uses data obtained from a survey of 120 Tunisian beekeepers. The findings from the partial least squares analysis highlight the value and complementarity of the three models (TPB, PMT, and extended PMT), with the extended model offering superior explanatory and predictive power. The TPB model reveals the significant influence of perceived behavioral control and attitudes toward climate change resilience strategies on the intention to adopt them. The PMT model emphasizes the roles of self-efficacy, coping appraisal, and the perception of climate change occurrence in shaping adoption intentions, with self-efficacy being the most impactful factor. The extended PMT model further demonstrates that self-efficacy strongly influences perceived behavioral control. Overall, all three models show a positive and significant impact of intention on the selection of specific resilience strategies.